The impact of social network marketing, price and trust on online consumer purchasing behaviour - Kozic, Jasmina (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2016)
Online social networks, as a phenomenon, around the globe have formed and established a platform for interaction and communication among people. This platform, due to its online features, has created a functional way for individuals to share their knowledge, opinions and ideas among each other, which makes a possibility for direct impact on people's behaviour in terms of communication and purchasing. Hence, this study attempted to observe and discuss the effects of social network marketing, price and trust on online consumer purchasing behaviour. Moreover, the moderation effect of income related with price as the independent variable and online consumer purchasing behaviour as the dependent variable was examined. The study was carried out by taking a sample of 235 respondents. A survey method using a structured questionnaire has been used throughout this research as a collection tool for possible usable data. The Structural Equation Modelling (SEM) as a tool to estimate the effect of the factors on online consumer purchasing behaviour was used. The Partial Least Squares (PLS) technique was applied to analyse the casual relationships between constructs using the software application SmartPLS 2.0. The results revealed that social network marketing, price and trust have positively affected online consumer purchasing behaviour. Hence, all the measures were highly reliable. In addition, an income moderates the relationship between price and online consumer purchasing behaviour. It has been found that the high income level provides a greater profound effect on the relationship between price and online consumer purchasing behaviour. Finally, this research adds significant value to the respective field within the area investigated, from both the theoretical and managerial side. The present study assist marketers in different directions. From the theoretical side, the present study contributes to the body of knowledge on online consumer purchasing behaviour through the investigation of different factors that influence consumers and their online purchasing behaviour.